Pola Asuh Orang Tua Tunggal dalam Meningkatkan Minat Baca Anak di Desa Sukowiryo - Yuni Rahmawati Rosyidah; Andi Wapa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this study is 1) To describe the parenting patterns applied by single parents in increasing children's reading interest in Sukowiryo Village, Bondowoso District, Bondowoso Regency 2) To describe the inhibiting and supporting factors for single parents in increasing children's reading interest in Sukowiryo Village, Bondowoso District, Bondowoso Regency. This study uses a qualitative approach, this approach uses the natural environment as a direct source of data, is descriptive analytical, emphasizes the process rather than the results. The results of this study indicate that: 1) In the process of raising their children, two single parent families tend to use authoritarian, permissive and democratic parenting patterns in encouraging their children to be more active in reading so that their education can develop well. 2) a) The inhibiting factor for single parents in raising their children is the control of single parent families in the process of supervising and communicating with their children cannot be done fully every day due to time constraints. This also has an impact on children's learning/reading discipline. In addition, their unstable economic factors cause a lack of availability of reading materials for children, so that children do not maximize their learning. b) While the supporting factors for single parents in raising their sons or daughters are the self-acceptance and determination of the single parents that they have built and fixed to live their lives. They try their best to continue to pay attention to the continuation of their children's education.